STRATEGI MEDIA RELATIONS POLITISI UNTUK MERAIH POPULARITAS DI MEDIA MASSA - Lailiyah, Nuriyatul (Program Magister Ilmu Politik, Universitas Diponegoro, 2015)
A good relationship with the media is very important for anyone who wants to get positive publicity. Positive publicity is used to be consideredÂ hard to achieve. But politicians in the beginning have the potential news value. Unfortunately, not all politicians aware and use it optimally. We could easily see that there just a few members of House of Representatife that can appear positively in the media. This study aimed to examine the media relations strategy applied by politicians to gain popularity in the media. Research was conducted by interviewing popular members of Central Java House of Representative and journalists who used to interview them. The method used in this research was mixed methods that combines quantitative and qualitative method. The data collection techniques used content analysis and in-depth interviews. The results showed there are two main strategies that applied by the informans to do media relations. First, speak in their capacity and competence and uses accountable. Second, do media relations personally and professionally. While media relations activities undertaken by board members are shared activities, press gatherings, press conferences, sending articles and press releases, and taking interviews. Keywords: media relations, politicians, publicities